Secretome Profiling Reveals the Signaling Molecules of Apoptotic HCT116 Cells Induced by the Dietary Polyacetylene Gymnasterkoreayne B - Kang, Kyungsu; Song, Dae-Geun; Lee, Eun Ha; Lee, Kyung-Mi; Park, Young Gyun; Jung, Sang Hoon; Pan, Cheol-Ho; Nho, Chu Won (AMER CHEMICAL SOC, 2014)
Dietary polyacetylenes from various foods have been receiving attention as promising cancer chemopreventive agents. However, until now, the detailed molecular mechanism and the regulatory proteins underlying these effects have not been elucidated. We investigated the effects of gymnasterkoreayne B (GKB), a model dietary polyacetylene from wild vegetables, on the programmed cell death of HCT116 human colorectal cancer cells. GKB inhibited HCT116 cell proliferation by inducing apoptotic cell death. GKB treatment resulted in ROS accumulation, leading to the activation of both intrinsic and extrinsic apoptotic pathway. We also found that FN1, TGFBI, APP, SERPINE1, HSPD1, SOD1, TXN, and ACTN4 may act as secretory signaling molecules during GKB-induced apoptotic cell death using LC-MS/MS identification followed by spectrum counting, statistical calculation, and gene ontology analysis. The secretory proteins suggested in this study may be promising candidates involved in apoptotic cell death of cancer cells induced by GKB that warrant further functional study.
Keywords: COLON-CANCER; PROTEINS; INDUCTION; ACTIVATION; DEATH; COMPONENTS; EXPRESSION; VEGETABLES; INHIBITOR; CASPASE-3